Natural Rights among Spanish Inquisition and Constitution - Álvarez Cora, Enrique (Res Publica. Revista de Historia de las Ideas Políticas, 2015)
The paper analyses the rationalist conception of natural rights, and the differents trends that assumes its discourse in the Spanish Inquisition banned literature, as well as the evolution of its concept, and the juridical and political ways of interpretation in Spanish constitutionalism.
Keywords: Spanish Inquisition; natural laws; constitution.